(untitled) (Research, Society and Development, 2019)
The present study aims to develop thermosensitive membranes with an intelligent mechanism of adhesion/release and potent antimicrobial action for the treatment of wounds. The membranes were prepared by electrosynthesis of the thermosensitive hydrogel poly (N-isopropylacrylamide) (PNIPAm) in the presence of chitosan (CHI). The material obtained is constituted by a semi-interpenetrating polymer network (sIPN) of CHI and PNIPAm. The chitosan is a natural biopolymer with activity bactericidal, anti-inflammatory and healing action. The commercial chitosan used was previously characterized in terms of its average molar mass (0.9312 * 105 g mol-1) by viscosimetric method and degree of deacetylation (86.23%), through conductometric titration. The PNIPAm hydrogel was incorporated to CHI polymer chain by electrochemical method using cyclic voltammetry technique. The sIPN CHI-PNIPAm membrane obtained was characterized by Fourier Transform Infrared Spectroscopy using the Attenuated Total Reflectance (FTIR-ATR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). FTIR-ATR spectra confirmed the polymerization of PNIPAm in the presence of CHI. TGA curve showed that sIPN membrane obtained has a composition of 33% chitosan and 55% PNIPAm. DSC thermal analysis showed a lower Tg of sIPN CHI-PNIPAm membrane compared to Tg of PNIPAm hydrogel. The phase transition temperature (LCST) of the sIPN CHI-PNIPAm membrane was determined by Ultaviolet-visible spectroscopy (UV-vis) the value found was 32 ° C.